Towards quantifying energy saving strategies in big-box retail stores: A case study in Ontario (Canada). (January 2016) - Richman, Russell; Simpson, Rob
Highlights: Analysis of two big-box retail stores at the same site; an original 'traditionally' designed store and an 'energy efficient' replacement design. Each significant design element contributing to energy efficiency was analyzed using building energy simulation software. Using actual utility bills for each store, the replacement store used 44% less energy (normalized for floor area). The main energy reductions were achieved through alternative electrical strategies (primarily lighting) (39%) and alternative space heating strategies (61%). Abstract: This research focuses on energy-related initiatives implemented by one big-box retail chain in Canada. Through analysis of energy reduction strategies, the study compares the energy performance of two stores (an original store and its replacement store) adjacent to each other at the same location. One of which operated with conventional design features and the other operated with energy-reducing upgrades. The results of this research conclude that the store constructed with advanced technological solutions outperformed the original store in terms of energy-use intensity by 44%. The main energy reductions were achieved through alternative electrical strategies (primarily lighting) (39%) and alternative space heating strategies (61%). The research also reveals that premium costs related to the advanced technologies were effective choices.